Enabling data storage and availability of multimodal neuroimaging studies: a NoSQL based solution - Fernandes, Filipe (2016)
Multimodal neuroimaging studies are of major interest in the clinical and research setting, enabling the combined study of the structure and function of the human brain. However, the amount of procedures applied, associated with the production of large volumes of data creates obstacles to the organization, maintenance and sharing of neuroimaging data. Taking this into account, we developed a NoSQL based solution that automates the process of organizing and sharing neuroimaging data. This system is composed by an application, which recognizes the files to be stored through the use of a standardized nomenclature of the files generated in the processing workflows. Additionally, the system is distributed in order to store data as documents enabling users to upload and retrieve files to/from the system in different locations. The prototype enhances the research process, through the simplification and reduction of the time spent organizing and sharing information.